(untitled) (Academicia Globe: Inderscience Research, 2024)
The oral cavity serves as a gateway to overall health, and the condition of the mucous membranes within it plays a crucial role in maintaining systemic well-being. This article explores the intricate relationship between diseases affecting the oral mucous membrane and their implications on the general health of the body. Understanding these connections is essential for comprehensive healthcare and highlights the importance of oral health in overall disease prevention and management.